Curative effect of the probiotic strain Lactobacillus fermentum L23 in a murine model of vaginal infection by Gardnerella vaginalis. (1st July 2014) - Daniele, M.; Pascual, L.; Barberis, L.
Abstract: Bacterial vaginosis is a common vaginal infection characterized by changes in the vaginal microbiota. The objective of this work was to evaluate the colonization ability and curative effect of Lactobacillus fermentum L23 after vaginal administration in female BALB/c mice infected with Gardnerella vaginalis . One dose of Lact. fermentum L23 containing 10 9 CFU ml −1 was administered locally in a murine vaginal model. L23 colonized the vaginal tract of BALB‐c mice after one inoculation. The infection by G. vaginalis in a murine model was induced by vaginal administration of a 1 × 10 6 CFU ml −1 suspension. Infection with the pathogen was observed in the vaginal tract for 4 days. At 144 h after inoculation, levels of 4 log10 CFU ml −1 were observed. The curative effect of L23 was evaluated with one administration at 1 × 10 9 CFU ml −1 72 h after the inoculation with G. vaginalis . Lactobacillus fermentum L23 inhibited the growth of G. vaginalis . The results of suppression of G. vaginalis using different concentrations of L23 were favourable due that these concentrations are normally used in commercial formulas. The obtained results indicate that Lact. fermentum L23 inhibited the growth of G. vaginalis . Therefore, L23 might be used as a potential biotherapeutic agent for the elimination of this bacterium. Significance and Impact of the Study: The use of the probiotic strain Lactobacillus fermentum L23 as a biotherapeutic agent can be expected to prevent and treat genital infections, particularly recurrent bacterial vaginosis, with similar concentrations to those normally used in commercial formulas. It is likely that the use of this probiotic strain for the treatment of bacterial vaginosis will provide a natural and nontoxic treatment modality.